Peran Institusi Ekonomi Dalam Menangani Eksternalitas Negatif Akibat Over Carrying Capacity Keramba Jaring Apung Waduk Jatiluhur - Elprida Sigiro, Ely; Azizah Rubianti, Nisa (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
This study aims to find out how externalities occur and the role of economic institutions in dealing with externalities of floating net cages in Jatiluhur Reservoir. The method used is descriptive qualitative analysis with secondary data on plot population numbers and water quality parameters in 2014-2019. The result of this study is that the increasing number of floating net cages plot populations causes over-carrying capacity, and negative externalities occur due to excessive leftover feed. The negative externality cause the reservoir water quality dicrease and disruption of activities around the Jatiluhur Reservoir. The study find, PJT II, the institution that have authority to manage Jatiluhur Reservoir, applies jurisdictional boundaries, rights, obligations, and representation rules to deal with negative externalities.